Normal and abnormal rhythms in the search for biological clocks: an epistemological gap between early twentieth-century biology and experimental psychology. - Shackelford, Jole (Annals of Science, 2026)
When American experimental psychologists began to study activity cycles in the early twentieth century, their research methods and interpretations of experimental results were guided by a commitment to behaviourism and neglected the work of biological rhythms researchers, now called chronobiologists, who approached behaviours from physiological and ecological perspectives, exploring activity and other rhythmic behaviours as governed by innate organic stimuli, biological clocks. The epistemological gap that developed between rhythms researchers and behavioural psychologists can be seen already in the work of Maynard S. Johnson and Curt P. Richter, both working with rodents in the 1920s and 1930s. This gap persisted into the 1960s, when psychologists began to realize that biological clocks help to explain some of their experimental results. This epistemological gap is plain from psychologists' reaction to the 1963 work of Michael Treisman, who was credited 50 years later with discovering the biological clock in humans, despite more than half a century of effort to study rhythms and locate clocks; recognition in the mid-1960s that clock-controlled circadian rhythms were useful in psychology began to close this gap.